Teachers’ work-family conflict in Malaysia : scale validation - Ismail, Zanariah; Nordin, Mohamad Sahari (Maryland Institute of Research (MIR), Maryland, USA, 2012)
There is the need for an evaluation instrument that can examine work-family conflict in Malaysia. Thus, this research aimed to verify the psychometric properties of the hypothesized measurement model of work-family conflict (WFC) scale in Malaysia. The aim of the current study was to test the psychometric properties of the work-family conflict 10-item index. To address this concern, 245 married female teachers were selected from 13 schools and a 10-item version of the work-family conflict was administered to them. The data were analyzed using the Confirmatory Factor Analysis (CFA) procedures. A second order CFA was used to test the framework of the total of 245 married female teachers data based on Structural Equation Modeling (SEM). The work-family conflict construct has shown to be a second-order construct which can be explained by two factors of the work-interfering-with-family conflict and family-interfering-with-work conflict. The result revealed that the hypothesized model for WFC that responses to the WFC scale can be explained by two-first order factors (wif and fiw) and one second-order factor (WFC).